Role-playing as a teaching-learning strategy to improve speaking skills in senior students at Abelardo Moncayo high school from Atuntaqui during 2021-2022 - Tamayo Santacruz, Blanca Alicia (2022)
Integrate role-playing as a teaching-learning strategy in the improvement of speaking skills in senior students at Abelardo Moncayo high school from Atuntaqui during the 2021-2022 academic year.